Crystal structures of (1,4,7,10-tetraazacyclododecane-κ(4) N)bis(tricyanomethanido-κN)nickel and (1,4,7,10-tetraazacyclododecane-κ(4) N)(tricyanomethanido-κN)copper tricyanomethanide - Luo, Jun (Acta Crystallogr E Crystallogr Commun, 2015)
The structures of two mononuclear transition-metal complexes with tricyanomethanide (tcm(−)) and 1,4,7,10-tetraazacyclododecane (cyclen) ligands, [Ni(C(4)N(3))(2)(C(8)H(20)N(4))], (I), and [Cu(C(4)N(3))(C(8)H(20)N(4))](C(4)N(3)), (II), are reported. In the neutral complex (I), the nickel cation is coordinated by one cyclen ligand and two monodentate N-bound tcm(−) anions in a distorted octahedral geometry. The tcm(−) ligands are mutually cis. The Cu(II) atom in (II) displays a distorted tetragonal–pyramidal geometry, with the four N-donor atoms of the cyclen ligand in the equatorial plane, and one tcm(−) anion bound through a single N atom in an axial site, forming a monocation. The second tcm(−) molecule acts as a counter-ion not directly coordinating to the copper cation. In both (I) and (II), extensive series of N—H⋯N and C—H⋯N hydrogen bonds generate three-dimensional network structures.